2009
DOI: 10.1007/s10517-009-0640-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition in Rats with Nonischemic Chronic Heart Failure

Abstract: The initial stages of nonischemic chronic heart failure in rats (model of oleothorax) were accompanied by the development of dyslipidemia. This state was characterized by an increase in total cholesterol concentration (due to the fraction of low-density lipoproteins) and atherogenicity index. The concentrations of plasma total cholesterol and low-density lipoproteins were shown to decrease in animals with severe course of nonischemic chronic heart failure. These changes were accompanied by a decrease in the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Physiological studies of haemodynamics per formed in CHF animals [10,11] have demonstrated that injection of silicon oil into each pleural sac causes the compression of pulmonary blood vessels and an increase of pressure in the area of pulmonary vein, thus leading to an increased load on the right atrium and ventricle. In addition, total fluid pressure on all parts of the myocardium occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological studies of haemodynamics per formed in CHF animals [10,11] have demonstrated that injection of silicon oil into each pleural sac causes the compression of pulmonary blood vessels and an increase of pressure in the area of pulmonary vein, thus leading to an increased load on the right atrium and ventricle. In addition, total fluid pressure on all parts of the myocardium occurs.…”
Section: Discussionmentioning
confidence: 99%
“…This study was per formed with male Wistar rats weighing 180-200 g. We used an adequate model that was developed for small Monoamine Metabolism in the Brain of Rats with Chronic Heart Failure of Non Ischemic Origin laboratory animals (rats) that allowed us to produce CHFs of different severities [10,11]. According to this method, we performed the intermittent injection of silicone oil into each pleural sac of the animals, which resulted in their gradually developing CHF.…”
Section: Methodsmentioning
confidence: 99%